ADIPOSE-DERIVED STEM CELL THERAPY ON NON-COMMUNICABLE DISEASE: A SYSTEMATIC REVIEW - Tandarto, Kevin; Oktarina, Caroline; Jonlean, Reganedgary; Irawan, Cosphiadi; Abdullah, Murdani; Purwoko, Reza Yuridian; Pawitan , Jeanne Adiwinata (Stem Cell Research and Development Center, Universitas Airlangga, 2023)
The increasing number of non-communicable diseases demands practical therapy innovations, including adipose-derived stem cell application. This study aimed to analyze the effectiveness of adipose stem cell therapy on non-communicable disease patients. The method used in this study was a systematic review according to PRISMA 2020 guidelines. The database search was done on PubMed, Google Scholar, Proquest, and the EBSCO host database between 2016 and 2021. ROBINS-I tool and RoB-2 were used to assess the risk of bias in the clinical trial study. The first literature search identified a total of 2615 articles. After exclusion for some reason, 6 articles were included in this systematic review study. A total of five studies were included in this study. Based on the risk of bias assessment of the included studies, it was found that all studies had a low risk of bias in all domains. This study showed that the efficacy of adipose-derived stem cell therapy was inconsistent; however, the results were promising. In addition, the results showed that adipose-derived stem cell therapy was safe without significant side effects. Further study was needed to identify therapeutic strategies based on Evidence-based Medicine (EBM).